Early diagnosis, effective treatment: modern approaches to the management of ectopic pregnancies - Ada Żydek; Urszula Ciułek; Wiktoria Bilska; Wiktoria Zduńczyk; Anna Dobosz; Michalina Dubińska; Wiktoria Paduch-Jakubczyk (Nicolaus Copernicus University in Toruń, 2024)
Purpose of research: The aim of this article is to provide an overview of the diagnosis and management of atypical ectopic pregnancy, with particular reference to pregnancy in the cesarean scar. The importance of early detection and medical intervention will be described, as well as the impact of advanced diagnostic techniques and modern treatments on the curability of patients.This article aims to provide valuable insights into the development of effective strategies for the diagnosis, treatment and prognosis of ectopic pregnancy. State of knowledge: Ectopic pregnancies account for 1-2% of all pregnancies, with the majority (90%) occurring in the fallopian tube. Less commonly, they present as ovarian, cervical or abdominal pregnancies. Advances in diagnosis and treatment have made it possible to identify rare forms such as cesarean scar pregnancy (0.15% of all pregnancies), interstitial pregnancy and recurrent ectopic pregnancy on tubal remnants. Techniques such as transvaginal ultrasound (TVS), MRI and laparoscopy have the potential to improve diagnostic accuracy and treatment outcomes. Modern interventions such as transvaginal natural orifice transluminal endoscopic surgery (vNOTES) and methotrexate have shown promise in terms of safety and efficacy. Conclusions: Ectopic pregnancy and its complications have a significant impact on the psycho-physical health of patients, requiring ongoing research to improve diagnostic and therapeutic methods. Future studies should focus on long-term outcomes and the coordination of multidisciplinary medical care to further improve diagnosis and treatment.